Proceedings of the ACM SIGGRAPH Symposium on Applied Perception in Graphics and Visualization 2011
DOI: 10.1145/2077451.2077465
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric distance perception in real and HMD-based virtual environments

Abstract: We conducted four experiments on egocentric depth perception using blind walking with a restricted scanning method in both the real and a virtual environment. Our viewing condition in all experiments was monocular. We varied the field of view (real), scan direction (real), blind walking method (real and virtual), and selfrepresentation (virtual) over distances of 4 meters to 7 meters. The field of view varied between 21.1 • and 13.6 • . The scan direction varied between near-to-far scanning and far-to-near sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
4
26
0
1
Order By: Relevance
“…It extends previous work on spatial perception in VEs (Ellis and Menges, 1998;Waller et al, 1998;Loomis and Knapp, 2003;Thompson et al, 2004;Interrante et al, 2008;Ries et al, 2008;Phillips et al, 2009Phillips et al, , 2010Mohler et al, 2010;Lin et al, 2011) by suggesting an experimental task in which participants are asked to learn and recall a series of object configurations in concurrently occupied virtual and real environments.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It extends previous work on spatial perception in VEs (Ellis and Menges, 1998;Waller et al, 1998;Loomis and Knapp, 2003;Thompson et al, 2004;Interrante et al, 2008;Ries et al, 2008;Phillips et al, 2009Phillips et al, , 2010Mohler et al, 2010;Lin et al, 2011) by suggesting an experimental task in which participants are asked to learn and recall a series of object configurations in concurrently occupied virtual and real environments.…”
Section: Discussionsupporting
confidence: 71%
“…The experimental task involves several judgments, including distance estimation, and it is not clear exactly what strategies participants use to learn object locations (Hartley et al, 2004). Previous work has shown that distance estimation is impaired within immersive VR, although including a self-avatar and increasing confidence in fidelity can reduce this impairment (Loomis and Knapp, 2003;Thompson et al, 2004;Interrante et al, 2006Interrante et al, , 2008Ries et al, 2008Ries et al, , 2009Phillips et al, 2009Phillips et al, , 2010Mohler et al, 2010;Lin et al, 2011). Our results suggest that the level of immersion is extremely important for accurate object location learning and recall, and that higher environmental fidelity may reinforce learning transfer from VEs to the real world.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol was the same as Experiment Four in Lin et al [2011] except for the viewing condition. In this experiment, subjects performed two methods of blind walking: direct blind walking and indirect blind walking .…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a followup experiment to the work of Lin et al [2011]. The experimental protocol was the same as that of Experiment Four in Lin et al [2011] except the viewing condition was binocular instead of monocular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation